Midazolam-sirupus, formulation and pharmacodynamic efficacy - K. Goracinova; K. Mladenovska; O. Gelevska; E. Fredro-Kumbaradzi; M. Glavas-Dodov; J. Nanceva (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2002)
Due to its pharmacokinetic and pharmacodynamic properties (sedation, amnesia and relief of anxiety) Midazolam has become a comm only used agent for conscious sedation of children before diagnostic or therapeutic procedure or before induction of anesthesia. Con sidering the advantage of oral administration to avoid the additional trauma of starting an IV in the child, and the fact that there is no ad equate dosage form (Midazolam - Syrupus) on the drug market in our country, the aim of the presented work was to formulate syrupus using syrupus b ase/aqueous solution of viscosity enhancer - HPMC, in combination with suitable sweetener, flavor, and preservatives, and to evaluate its q uality and stability. The pharmacodynamic efficacy/sedative effect of Midazolam HCl - Syrupus formulation was evaluated in 33 pediatric patients comp aring this with the efficacy of intramuscularly administered Midazolam HCl (35 pediatric patients) in accordance with the Ramsay scale for analgosedation. The formulation manifested good quality in respect to physical properties, physico-chemical parameters (pH value, relative dens ity, drug content, ingredients content) antimicrobial efficacy and microbiological quality according to Ph Eur 3. In the conditions chara cteristic of the second (II) climate zone, the dosage form was stable for four months. The sedative effect of orally administered Midazolam was manifested in a period necessary for surgical premedication (30 - 45 min). The majority of patients (71%) entered the second phase on the Ramsa y scale, when Midazolam was administered in a dose of 0.40 mg/kg.